Optimization of the clinical course of stable angina pectoris with the use of omega-3 polyunsaturated fatty acids and combined magnetotherapy - Zolotarova, K. O. (Journal of Education, Health and Sport, 2016)
The article presents the results of the study of the comparative efficacy of the protocol for angina pectoris medication and combined therapy with the use of ω-3 PUFA and magnetotherapy on the dynamics of the frequency of anginal attacks of patients with stable angina. It was found that the use of ώ-3 PUFA and MT in therapy allows a significantly higher and further reduction in the frequency of attacks compared with standard therapy, and this effect is largely due to the influence of MT and to a lesser extent - the effect of omega-3 polyunsaturated fatty acids.